Association between vitamin D status and long‐term falls‐related hospitalization risk in older women. Issue 11 (10th September 2021) - Sim, Marc; Zhu, Kun; Lewis, Joshua R.; Hodgson, Jonathan M.; Prince, Richard L.
Abstract: Background: The dose–response relationship of vitamin D status and the risk of serious falls requiring hospitalization in older women is unclear. We examined the association between plasma 25‐hydroxyvitamin D (25OHD) with falls‐related hospitalizations over 14.5 years in a large cohort of older women. Methods: In 1348 community‐dwelling Australian women aged ≥70 years, plasma 25OHD concentrations were assessed at baseline (1998) using LC–MS/MS. Fall‐related hospitalizations were obtained from linked data systems. Baseline grip strength and timed‐up‐and‐go (TUG) were assessed as measures of muscle strength and physical function, respectively. Results: Mean plasma 25OHD was 66.9 ± 28.2 nmol/L. The number of women in the low (LOW; <50 nmol/L), medium (MED; 50 to <75 nmol/L), and higher 25OHD (HIGH; ≥75 nmol/L) categories were 384 (28.5%), 491 (36.4%), and 473 (35.1%), respectively. In the multivariable‐adjusted analysis, compared to LOW, women in HIGH had significantly lower hazards for a falls‐related hospitalization (HR 0.76 95%CI 0.61–0.95). Restricted cubic spline regression models highlight increasing gradient of risk for a falls‐related hospitalization with decreasing 25OHD levels. Generalized additive modeling highlighted higher 25OHD to be associated with better TUG performance. Including TUG into the multivariable‐adjusted models did not alter the relationship between 25OHD and injurious falls (HIGH vs. LOW HR 0.76 95%CI 0.60–0.95). Conclusions: In community‐dwelling older Australian women, maintaining plasma 25OHD at 75 nmol/L or above may confer benefits to muscle function and long‐term prevention of injurious falls requiring hospitalization. This relationship appears to be independent of better physical function observed in women with higher 25OHD levels.